Enhancement of Anatomical Education Using Augmented Reality: An Empirical Study of Body Painting. Issue 6 (19th February 2019) - Barmaki, Roghayeh; Yu, Kevin; Pearlman, Rebecca; Shingles, Richard; Bork, Felix; Osgood, Greg M.; Navab, Nassir
Abstract : Students in undergraduate premedical anatomy courses may experience suboptimal and superficial learning experiences due to large class sizes, passive lecture styles, and difficult‐to‐master concepts. This study introduces an innovative, hands‐on activity for human musculoskeletal system education with the aim of improving students' level of engagement and knowledge retention. In this study, a collaborative learning intervention using the REFLECT (augmented reality for learning clinical anatomy) system is presented. The system uses the augmented reality magic mirror paradigm to superimpose anatomical visualizations over the user's body in a large display, creating the impression that she sees the relevant anatomic illustrations inside her own body. The efficacy of this proposed system was evaluated in a large‐scale controlled study, using a team‐based muscle painting activity among undergraduate premedical students ( n  = 288) at the Johns Hopkins University. The baseline knowledge and post‐intervention knowledge of the students were measured before and after the painting activity according to their assigned groups in the study. The results from knowledge tests and additional collected data demonstrate that the proposed interactive system enhanced learning of the musculoskeletal system with improved knowledge retention ( F (10, 133)  = 3.14, P  < 0.001), increased time on task ( F (1, 275)  = 5.70, P  < 0.01), and a high level of engagement ( F (9, 273)  = 8.28, P  < 0.0001). The proposed REFLECT system will be of benefit as a complementary anatomy learning tool for students.